2008
DOI: 10.3177/jnsv.54.339
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Polymorphism of Thiaminase I in Seawater Fish

Abstract: Summary Thiaminase I from the seawater fish Fisturalia petimba was characterized, and pI polymorphism of the enzyme was first described, together with the active subfragment of thiaminase I. The liver of F. petimba contained thiaminase I of at least three different pIs and the major fraction exhibited pI 5.7. The most evident difference among pI isozymes was the size of the active subfragments into which they were dissociated. pI 5.7 enzyme dissociated into subfragments of 25 kDa, while pI 7-9 enzymes dissocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Several studies suggest an internal regulatory mechanism for thiaminase activity in fish that would also be consistent with de novo thiaminase production; factors reported to influence thiaminase activity in prey fish are diet, stress from being held in the laboratory, and pathogen challenge by a bacterial species that does not contain thiaminase activity (Lepak et al 2008;Wistbacka et al 2009;Honeyfield et al 2010). Furthermore, putative thiaminase enzymes purified from two fish species showed no amino acid sequence homology to bacterial enzymes or to each other, consistent with speciesspecific sources of thiaminase activity (Boś and Kozik 2000;Nishimune et al 2008).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies suggest an internal regulatory mechanism for thiaminase activity in fish that would also be consistent with de novo thiaminase production; factors reported to influence thiaminase activity in prey fish are diet, stress from being held in the laboratory, and pathogen challenge by a bacterial species that does not contain thiaminase activity (Lepak et al 2008;Wistbacka et al 2009;Honeyfield et al 2010). Furthermore, putative thiaminase enzymes purified from two fish species showed no amino acid sequence homology to bacterial enzymes or to each other, consistent with speciesspecific sources of thiaminase activity (Boś and Kozik 2000;Nishimune et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…The true source of thiaminase activity in aquatic ecosystems remains elusive. Potential sources that merit further investigation include non-P. thiaminolyticus bacteria, de novo synthesis by lower trophic-level food items such as zooplankton or mussels, and de novo synthesis of thiaminase by fishes (Deolalkar and Sohonie 1954;Boś and Kozik 2000;Nishimune et al 2008). Many potential bacterial sources of thiaminase activity exist, and comparing the composition of the bacterial flora in fish viscera with and withou thiaminase activity would be useful for determining if particular bacterial species are associated with increased thiaminase activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, acute short-lived thiamine starvation may have less toxicity, and could potentially be achieved by administration of an enzyme such as thiaminase I. Thiaminase catabolizes thiamine and can cause acute thiamine deficiency. Several forms of the enzyme thiaminase exist in nature, including plant, animal and bacterial forms of the enzyme [4, 14, 15]. Since thiamine is an essential vitamin and since thiamine in excess is not known to be toxic, the physiologic role of thiaminase is not known [5].…”
Section: Discussionmentioning
confidence: 99%
“…Protein chemistry investigations provided additional evidence for de novo synthesis of thiaminase I by fish. Partial purifications of thiaminase I enzymes from bacteria, fish, and a variety of crustaceans suggested that thiaminase I biochemical properties, including molecular mass, substrate specificity, and co-substrate specificity, varied depending on the source 26 , 27 . Fish and shellfish thiaminase I were more different from bacterial thiaminase I than from each other, and thiaminase I from different bacteria were usually more similar to one another than to thiaminase I of other taxa 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%